O voo do idoso - Bertulucci, José Alberto Cesar (2017)
Comfort on board for passenger well-being has become a top priority for airlines in this 21st century. Certainly, ambitioning to adapt to take advantage of the reality nowadays experienced with the rapid aging of the world’s population. Regardless if on a long or short trip, it is likely that those who suffer most from the effects of an air trip are the elderly who, in addition to all the discomfort due to bad flight conditions, have not yet acquired the right to required special treatments, which are guaranteed by law to them. In certain problem-situations, questions arise: how should a flight attendant act, for example, when an elderly passenger needs to go to the toilet immediately, when everyone has to be, for safety, with the belt fastened? How to reconcile safety and comfort of passengers, at all times, on board the planes? The objectives of this study are: (i) to reflect on the environmental conditions of an airplane cabin, offered to the elderly during a flight, (ii) to investigate problematic, unpleasant or conflicting situations involving an elderly, dependent or independent, in an airplane; (iii) Forward a proposal based on preventive strategies in favor of a controlled environment, i.e, thought for/prepared for the welfare of an elderly person. The methodology required a survey and analysis of theoretical texts that deals with the themes and gives base to this study, such as the rights of the elderly in the most varied environments, the problems brought up by the advancement of the age and that require a special treatment, etc. The expected results are that: (i) Bring up the need of making detailed diagnoses of each of the problem-situations, by listening to the elderly themselves, so that the period confined in a cabin becomes more comfortable to the long-lived passengers; (ii) the efforts undertaken in this study can serve as a guide to new procedures for elderly passengers, precisely in order to ensure that in-flight environmental conditions are met by the necessary technological upgrading of new generations of airplanes, as well as the proper training of on-board staff on aging